Sea lampreys elicit strong transcriptomic responses in the lake trout liver during parasitism. (December 2016) - Goetz, Frederick; Smith, Sara; Goetz, Giles; Murphy, Cheryl
Abstract Background The sea lamprey (Petromyzon marinus ) is a jawless vertebrate that parasitizes fish as an adult and, with overfishing, was responsible for the decline in lake trout (Salvelinus namaycush ) populations in the Great Lakes. While laboratory studies have looked at the rates of wounding on various fish hosts, there have been few investigations on the physiological effects of lamprey wounding on the host. In the current study, two morphotypes of lake trout, leans and siscowets, were parasitized in the laboratory by sea lampreys and the liver transcriptomes of parasitized and nonparasitized fish were analyzed by RNA-seq (DESeq2 and edgeR) to determine which genes and gene pathways (Ingenuity Pathway Analysis) were altered by lamprey parasitism. Results Overall, genes encoding molecules involved in catalytic (e.g., enzymatic) and binding activities (factors and regulators) predominated the regulated gene lists. In siscowets, the top upregulated gene wasgrowth arrest and DNA-damage-inducible protein and for leans it wasinterleukin-18-binding protein. In leans, the most significantly downregulated gene wasUDP-glucuronosyltransferase 2A2 - DESeq2 orphosphotriesterase related - edgeR. For siscowets, the top downregulated gene wasC-C motif chemokine 19 - DESeq2 orGTP-binding protein Rhes - edgeR. Gene pathways associated with inflammatory-related responses or factors (cytokines, chemokines, oxidative stress, apoptosis) were regulated following parasitism in both morphotypes. However, pathways related to energy metabolism (glycolysis, gluconeogenesis, lipolysis, lipogenesis) were also regulated. These pathways or the intensity or direction (up/downregulation) of regulation were different between leans and siscowets. Finally, one of the most significantly downregulated pathways in both leans and siscowets was the kynurenine (tryptophan degradation) pathway. Conclusions The results indicate a strong transcriptional response in the lake trout to lamprey parasitism that entails genes involved in the regulation of inflammation and cellular damage. Responses to energy utilization as well as hydromineral balance also occurred indicating an adjustment in the host to energy demands and osmotic imbalances during parasitism. Given the role of the kynurenine pathway in promoting immunotolerance in mammals, the downregulation observed in this pathway during parasitism may signify an attempt by the host to inhibit any feedback suppression of the immune response to the lamprey.